Digitalizing Cash Waqf Linked Sukuk: Integrating Social Finance, Green Finance, And Technological Innovation - Rachmawaty, Rachmawaty; Hamsinah, Hamsinah; Holiawati, Holiawati (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
The increasing demand for sustainable and socially responsible financial instruments has led to the development of innovative solutions that combine social and green finance. This paper explores the integration of Cash Waqf Linked Sukuk (CWLS) with cutting-edge digital technologies to enhance its potential as a transformative instrument in Islamic finance. CWLS combines Islamic principles of waqf (endowment) and sukuk (bonds) to mobilize resources for socially beneficial projects while addressing environmental sustainability. This study emphasizes how the digitalization of CWLS—through technologies like blockchain, fintech, and data analytics—can enhance transparency, streamline operations, and expand its reach globally. The study employs a systematic literature review and bibliometric analysis using VOS viewer to map and analyze existing research trends, knowledge clusters, and emerging themes related to CWLS. The findings highlight the potential of CWLS as a sustainable financial instrument that aligns with the principles of distributive justice while addressing global environmental challenges. Bibliometric analysis reveals significant research gaps and key contributors in this domain, providing a foundation for future studies. The findings highlight the growing potential of CWLS to drive socio-economic inclusion and environmental stewardship, demonstrating its relevance in the evolving landscape of sustainable finance. Recommendations are provided for waqf managers to adopt digital tools for improving fund management, for waqif to understand the dual benefits of their contributions, and for policymakers to create regulatory frameworks that support the scaling of CWLS projects. These insights are critical for stakeholders seeking to harness CWLS as a vehicle for sustainable finance